Uso de consideraciones científicas para predicción dimensional de máquina secadora de abono orgánico - Hernandez Vasquez, Adan Paolo (2016)
In this research it is to select and find the main dimensions of a dryer for organic fertilizer, produced by the company BIOFERT SAC, from a Lagrangian perspective developed in previous studies, which combine heat transfer and mass movement of a individual particle through the dryer. In the first part of the study, a selection process dryer develops, if it is true not only a dryer is right, will choose whichever is more suitable for the type of material to be dried, then a thermodynamic analysis develops dryer to obtain a mass flow and air properties required for drying certain amount of moist product. an algorithm that associates the physical properties of the material with the mass transfer and heat, and has as output the main dimensions of drier (such as diameter and length) is then established. the EES (Engineering Equations Solver) software is a tool widely used in the area of thermal fluids are used in this work because, apart from its quality solver, has predefined functions that allow access to the thermodynamic and transport properties of many substances for solving equations. The results indicate that the most suitable for this type of work dryer, rotary dryer is the parallel flow whose diameter is 1.23 m and whose length is 6.26m.